PENGEMBANGAN E-MODUL BERBASIS FLIPBOOK UNTUK MENINGKATKAN SIKAP TANGGUNG JAWAB PADA MATA PELAJARAN PKN KELAS V - Sumaryati, Bernadeta; Sunaryati, Titin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study was to develop a flipbook-based e-module and evaluate its feasibility and efficacy in improving the responsible attitudes of fifth grade elementary school students. This study was conducted at SDN Jayamukti 04 Cikarang Pusat in the 2023–2024 academic year. This kind of study is known as R&D (study and Development) research, and it uses the ADDIE model as its development paradigm. This study involved thirty-three students in class V. Creation of a Flipbook-Based E-Module to Enhance Students' Responsible Attitudes in Class V Elementary School Pancasila Education Learning Based on the percentage formula used to gauge the validity of the Flipbook-Based E-Module, experts were able to acquire assessment results. According to the findings of the evaluation by language experts, which included the criteria